A "Unique Experiment": The Ontario Labour Court, 1943-1944 - Munro, Katherine (Labour / Le Travail, 2014)
Argues that the short-lived Ontario Labour Court of 1943-44 set the stage for Canada's collective bargaining regime since the Second World War. Contrasts Canadian labour relations at the time with that in the US under the Wagner Act. Analyzes landmark cases and administration of the Ontario collective bargaining act under which the court was created, as well as providing brief bios of prominent lawyers and judges. Emphasizes that the court arose from common-law precepts of the primacy of property rights. Takes note of the strong opposition to unions and collective bargaining, especially among employers. Concludes that while labour made gains in some areas, the court's mixed record of achievement also included constraints on legal striking and fragmentation of the union movement. An appendix of court decisions on union certification is included.
Keywords: Canada; Collective bargaining; Government policy; History; Industrial relations; LABOR arbitration; LABOR courts; LABOR laws & legislation; LABOR unions – Law & legislation; Labor Unions